Planning and Cost Analysis of Washing Porang Subber on Combination Machine for Washing and Cutting Porang Tuber - Liza Rusdiyana; Nanda Ela Sasmita; Nur Husodo; Eddy Widiyono; Muhammad Lukman Hakim; Rizaldy Hakim (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2021)
The cleaning process plays an important role in producing hygienic porang tubers, so that later chips and porang flour have good quality. Currently, the home industry for processing porang tubers still uses a simple method, namely using a manual washing machine so that it requires a lot of energy and a long time. One alternative to increase efficiency and productivity is to make a porang tuber washing machine.In planning this machine, it begins with field studies and literature. Planning in designing this machine includes planning for motor power, shaft, bearing, pulley-belt, sprocket-chain and budget design, after calculating and getting results it is necessary to conduct experiments to get conclusions from this machine.In planning the calculation of the machine, it requires a motor power of 2.2 HP with a motor rotation of 1400 rpm and a shaft rotation of 35 rpm, a force of 25.6 N, a torque of 1.920 N.mm, the selling price of the tool is Rp. 15,970,000 and the payback period is achieved in 228.4 days or 28.5 weeks or 7.1 months